2012
DOI: 10.1111/j.1365-2966.2012.20517.x
|View full text |Cite
|
Sign up to set email alerts
|

A giant radio flare from Cygnus X-3 with associated γ-ray emission

Abstract: With frequent flaring activity of its relativistic jets, Cygnus X‐3 (Cyg X‐3) is one of the most active microquasars and is the only Galactic black hole candidate with confirmed high‐energy γ‐ray emission, thanks to detections by Fermi Large Area Telescope (Fermi/LAT) and AGILE. In 2011, Cyg X‐3 was observed to transit to a soft X‐ray state, which is known to be associated with high‐energy γ‐ray emission. We present the results of a multiwavelength campaign covering a quenched state, when radio emission from C… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
86
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(94 citation statements)
references
References 53 publications
8
86
0
Order By: Relevance
“…In both cases the GeV emission is most likely produced by inverse Compton scattering on stellar photons (Fermi LAT Collaboration et al 2009;Dubus et al 2010). However, contrarily to Cygnus X-1, the conditions required to detect gamma rays from Cygnus X-3 are that the source is in the SS and showing significant emission (0.2-0.4 Jy) with rapid variations in the radio flux from the radio jets (Corbel et al 2012). The latter is probably related to strong shocks (probably due to discrete jet ejections) occurring when the source undergoes state transitions in and out of the ultra-SS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In both cases the GeV emission is most likely produced by inverse Compton scattering on stellar photons (Fermi LAT Collaboration et al 2009;Dubus et al 2010). However, contrarily to Cygnus X-1, the conditions required to detect gamma rays from Cygnus X-3 are that the source is in the SS and showing significant emission (0.2-0.4 Jy) with rapid variations in the radio flux from the radio jets (Corbel et al 2012). The latter is probably related to strong shocks (probably due to discrete jet ejections) occurring when the source undergoes state transitions in and out of the ultra-SS.…”
Section: Discussionmentioning
confidence: 99%
“…So far, the only microquasar (i.e. XRB displaying relativistic jets) firmly detected at high energies (> 100 MeV) is Cygnus X-3 (Tavani et al 2009;Fermi LAT Collaboration et al 2009) and its gamma-ray emission is related to the formation/existence of the radio jets (Piano et al 2012;Corbel et al 2012). However Malyshev et al (2013) showed there is a 4σ-level evidence of gamma-ray signal for Cygnus X-1, above 100 MeV, in 3.8 yr of Fermi-LAT data, only when the source is in the HS.…”
Section: Introductionmentioning
confidence: 99%
“…This microquasar consists of a Wolf-Rayet star and a compact object (most likely a black hole), and shows frequent and strong flaring activity. The Cyg X-3 multi-wavelength monitoring campaign reported by Corbel et al (2012) shows a sharp transition from a quenched state to a major flare, with an onset estimated at MJD 55641.0±0.5 (i.e. March 21).…”
Section: Data Reductionmentioning
confidence: 99%
“…During 2006-2009 Cyg X-3 showed similar dependencies between soft (RXTE ASM), hard (Swift/BAT) X-rays and radio emission ( [1,6,[8][9][10]). Gamma-ray emission was detected during the flaring states ( [11,12]).…”
Section: Monitoring Program Of Microquasars With the Ratan-600 Telescopementioning
confidence: 94%